Comparative analysis of cross-platform development methodologies: a comprehensive study - Raiymbek Jangassiyev; Zhanat Umarova; Aisaule Ussenova; Zlikha Makhanova; Nurlybek Zhumatayev; Manat Amirov; Gulzhan Koishibekova (Universitas Ahmad Dahlan, 2025)
In an era marked by the proliferation of devices and operating systems, delivering native-feeling applications across platforms has become indispensable. This paper scrutinizes native development through the lens of cross-platform frameworks, investigating their merits, major contenders such as React Native, Flutter, Xamarin, and the nascent .NET MAUI, and their practical implementations. By dissecting the distinct strengths and considerations of each framework, we provide developers with insights to make judicious decisions commensurate with their requirements and proficiencies. This inquiry underscores how cross-platform frameworks empower developers to broaden their audience reach while upholding native performance standards, thereby shaping the trajectory of app development through sustained innovation and integration with emergent technologies.